STRATEGI PENGELOLAAN KEUANGAN UNTUK PERTUMBUHAN UMK (STUDI KASUS DESA BANGUN JAYA) - Panjaitan, Sherly Lasmian Samaria; Seprini, Seprini; Makmur, Makmur (Gapenas Publisher, 2025)
This study aims to analyze financial management strategies for SME growth (Case Study of Bangun Jaya Village). The type of research is qualitative. The informants in this study are 20 individuals (10 informants are micro-business owners and 10 informants are small-business owners). The data analysis method used in this study is SWOT analysis. The results of this study indicate that SME financial management is still simple and poorly documented, particularly in micro businesses. Micro businesses tend not to keep financial records, do not prepare budgets, and use profits directly for household consumption. In contrast, small businesses have begun to implement cash flow tracking, profit and loss statements, separation of personal and business cash, as well as short-term and long-term planning.